2018
DOI: 10.1051/e3sconf/20182600003
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of processing InSAR Sentinel-1A/B data for correlation of mining subsidence with mining induced tremors in the Upper Silesian Coal Basin (Poland)

Abstract: Abstract. The Satellite Radar Interferometry is one of the common methods that allow to measure the land subsidence caused by the underground black coal excavation. The interferometry images processed from the repeat-pass Synthetic Aperture Radar (SAR) systems give the spatial image of the terrain subjected to the surface subsidence over mining areas. Until now, the InSAR methods using data from the SAR Systems like ERS-1/ERS-2 and Envisat-1 were limited to a repeat-pass cycle of 35-day only. Recently, the ESA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Thus, we do not describe interferometric principles in this work. Many studies have demonstrated the effective application of DInSAR for monitoring fast terrain displacements [4][5][6][7][8]. DInSAR provides reliable results when the displacement rate is much higher than atmospheric artifacts [35].…”
Section: Multi-temporal Consecutive Dinsar Processingmentioning
confidence: 99%
“…Thus, we do not describe interferometric principles in this work. Many studies have demonstrated the effective application of DInSAR for monitoring fast terrain displacements [4][5][6][7][8]. DInSAR provides reliable results when the displacement rate is much higher than atmospheric artifacts [35].…”
Section: Multi-temporal Consecutive Dinsar Processingmentioning
confidence: 99%
“…Sci. 2018, 8, x FOR PEER REVIEW 2 of 11 In most coal fields in China, the mined-out regions are enriched by water, which led to frequent accidents and the serious destruction of ecological environment and serious threat to coal-mining practices [8,15,16]. Therefore the detection of the mined-out areas, especially the water-filled minedout area in advance, is one of the most important issues [17].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, the region suffers from several seismic events exceeding a magnitude of Mw 4.0. Some of these tremors result in recorded ground-surface subsidences [2,3], most of which are located in already existing subsidence troughs. Figure 3 shows the sum of subsidences (LOS) calculated for the period of 2014-2018.…”
Section: Legnica-glogow Copper Belt Areamentioning
confidence: 99%
“…Synthetic aperture radar interferometry (InSAR) allows the detection of ground-surface changes in a very wide range, from anthropogenic [1][2][3][4] and natural [5][6][7] events having limited spatial range and amplitude, to events having a wider, regional range [8][9][10]. As is the case with any measurement method, the InSAR (differential InSAR (DInSAR), persistent scatterer InSAR (PSInSAR), or small baseline subset (SBAS)) methods also have significant limitations [11].…”
Section: Introductionmentioning
confidence: 99%